PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DAN PENGGUNAAN GAME EDUKASI BERBASIS AI TERHADAP MINAT BELAJAR MATEMATIKA SISWA MIS AL BASHIRAH - Sahriani Saskia Malisa; Ansar; Hasan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is an experimental study with a quantitative approach aimed at determining the influence of the Numbered Heads Together (NHT) cooperative learning model on students' interest in learning mathematics, the influence of using AI-based educational games on students' interest in learning mathematics, and the influence of the interaction between the Numbered Heads Together (NHT) cooperative learning model and the use of AI-based educational games on students' interest in learning mathematics at MIS Al Bashirah. The research design used is a 2x2 factorial design. The population in this study amounted to 520 students, with a sample of 93 students divided into 4 classes, namely; VA (23 students), VB (23 students), VC (23 students), and VD (24 students). Data collection techniques used questionnaires and observation. Data analysis employed descriptive statistical analysis and inferential statistical analysis. The results showed that; 1) there is a significant influence of the Numbered Heads Together (NHT) cooperative learning model on students' interest in learning mathematics, with a significance value of 0.000 < 0.05. 2) there is a significant influence of the use of AI-based educational games on students' interest in learning mathematics, with a significance value of 0.000 < 0.05. 3) there is a significant interaction between the Numbered Heads Together (NHT) cooperative learning model and the use of AI-based educational games on students' interest in learning mathematics, with a significance value of 0.046 < 0.05 at MIS Al Bashirah.